Requirement of Mucosa‐Associated Lymphoid Tissue Lymphoma Translocation Protein 1 Protease Activity for Fcγ Receptor–Induced Arthritis, but Not Fcγ Receptor–Mediated Platelet Elimination, in Mice. Issue 6 (26th April 2020) - Martin, Kea; Touil, Ratiba; Cvijetic, Grozdan; Israel, Laura; Kolb, Yeter; Sarret, Sophie; Valeaux, Stéphanie; Degl'Innocenti, Elena; Le Meur, Thomas; Caesar, Nadja; Bardet, Maureen; Beerli, Christian; et al.
Abstract : Objective: Fcγ receptors (FcγR) play important roles in both protective and pathogenic immune responses. The assembly of the CBM signalosome encompassing caspase recruitment domain–containing protein 9, B cell CLL/lymphoma 10, and mucosa‐associated lymphoid tissue lymphoma translocation protein 1 (MALT‐1) is required for optimal FcγR‐induced canonical NF‐κB activation and proinflammatory cytokine release. This study was undertaken to clarify the relevance of MALT‐1 protease activity in FcγR‐driven events and evaluate the therapeutic potential of selective MALT‐1 protease inhibitors in FcγR‐mediated diseases. Methods: Using genetic and pharmacologic disruption of MALT‐1 scaffolding and enzymatic activity, we assessed the relevance of MALT‐1 function in murine and human primary myeloid cells upon stimulation with immune complexes (ICs) and in murine models of autoantibody‐driven arthritis and immune thrombocytopenic purpura (ITP). Results: MALT‐1 protease function is essential for optimal FcγR‐induced production of proinflammatory cytokines by various murine and human myeloid cells stimulated with ICs. In contrast, MALT‐1 protease inhibition did not affect the Syk‐dependent, FcγR‐mediated production of reactive oxygen species or leukotriene B4 . Notably, pharmacologic MALT‐1 protease inhibition in vivo reduced joint inflammation in the murine K/BxN serum–induced arthritis model (mean area under the curve for paw swelling of 45.42% versus 100% in control mice; P = 0.0007) but did not affect platelet depletion in a passive model of ITP. Conclusion: Our findings indicate a specific contribution of MALT‐1 protease activity to FcγR‐mediated events and suggest that MALT‐1 protease inhibitors have therapeutic potential in a subset of FcγR‐driven inflammatory disorders.